2022
DOI: 10.1088/1755-1315/1020/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Analysis of Mangrove Leaves (Rhizophora apiculata) Soaking with Lime Water for Ruminants Feed

Abstract: Mangrove leaves (Rhizophora apiculata) has potential as animal feed because their had high protein content around 11,72%. Mangrove leaves contain anti-nutritional substances in the form of tannins. Tannins are antinutrient compounds that bind to proteins, carbohydrates (cellulose, hemicellulose and pectin), vitamins and minerals. Boiling can reduce the content of tannins and other anti-nutrients because phenolics are soluble in hot water and lime can hydrolyze tannins causing the active phenolic tannin groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In this study organic matter produced ranged from 90.00%-91.11%. The content of this organic material is not too different from research Sari et al (2022) results of proximate analysis organic matter of Mangrove Leaves (Rhizhopora apiculata) soaking with lime water around 91.14%-92.07%. High digestibility of organic matter in this study, it is suspected because dry matter digestibility in the study higher.…”
Section: Advances In Animal Andmentioning
confidence: 59%
See 2 more Smart Citations
“…In this study organic matter produced ranged from 90.00%-91.11%. The content of this organic material is not too different from research Sari et al (2022) results of proximate analysis organic matter of Mangrove Leaves (Rhizhopora apiculata) soaking with lime water around 91.14%-92.07%. High digestibility of organic matter in this study, it is suspected because dry matter digestibility in the study higher.…”
Section: Advances In Animal Andmentioning
confidence: 59%
“…Based on the table above, it was found that the higher used of mangroves in the treatment resulted in a high total phenol and tannin combination, this is based on previous research by Sari et al (2022) anti-nutritional substances contained in mangrove leaves in the form of tannins and another polyphenol compounds. The total phenol and tannin content are related because tannins are included in secondary metabolites synthesized on plants and classified as polyphenolic compounds and had ability to form complex compounds with another macromolecule.…”
Section: Effect Combination Of Hay Mangrove Leaves and Native Grass O...mentioning
confidence: 81%
See 1 more Smart Citation
“…The husk ash substrate can be used as a cheap and easily available NaOH replacement alkaline solution, this is in accordance with the opinion of Jamarun et al (2021) which explains that husk ash water functions as a base that is cheap and easily obtained in rural areas, it can be used as a substitute for NaOH. Furthermore, Sari et al (2022) also explained that hydrolysis with husk ash water is more profitable than other types of alkali. The use of processed avocado seeds with NaOH up to 20% does not interfere with quail performance, while above 20% causes quail performance to decline (Dahyuni 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For farmers in coastal areas, competition in land use is also a problem because the land is used for the tourism sector which is profitable in the short term. So that land for forage is limited, it is necessary to look for alternative feeds that are available in a sustainable manner (Sari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%